Answers

2016-04-22T20:04:57+05:30
Given, (x-1)/x = 15/4
         ⇒4(x-1) = 15x
         ⇒4x - 4 = 15x
         ⇒4x - 15x = 4
         ⇒-11x = 4
         ⇒ x = -4/11             ....eqn. 1
Now,
       (x-1)/x = 15/4
     Squaring both sides,
      ⇒{(x-1)/x}^2 = (15/4)^2
      ⇒(x^2 + 1 -2x)/x^2 = 225/16
    On adding 4x/(x^2) both sides and solving, you will get
     (x^2 + 1 + 2x)/(x^2) = 225/16 + 4x/(x^2)
    Now, SUBSTITUTE THE VALUE OF x WE GOT, IN RHS ONLY from eqn. 1. 
     And Solve... You will get
     ⇒(x^2 + 1 + 2x)/(x^2) = 49/16
     ⇒{(x+1)/x}^2 = (7/4)^2
     ∴ (x + 1)/x = 7/4 (Ans.)
    Please mark as brainliest....!!!!! Thank You. 
          
0